2010
DOI: 10.1016/j.expneurol.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous multipotent adult progenitor cell therapy for traumatic brain injury: Preserving the blood brain barrier via an interaction with splenocytes

Abstract: Recent investigation has shown an interaction between transplanted progenitor cells and resident splenocytes leading to modulation of the immunologic response in neurological injury. We hypothesize that the intravenous injection of multipotent adult progenitor cells (MAPC) confers neurovascular protection after traumatic brain injury through an interaction with resident splenocytes, subsequently leading to preservation of the blood brain barrier. Four groups of rats underwent controlled cortical impact injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
114
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 22 publications
12
114
1
Order By: Relevance
“…More recent studies have implicated vagus nerve activity, especially the efferent splenic component, in reducing systemic inflammation (Borovikova et al, 2000;Rosas-Ballina et al, 2008;Olofsson et al, 2012). Consistent with this, we have previously demonstrated that splenectomy markedly decreased TBI-triggered BBB permeability, suggesting a role for spleen-mediated systemic inflammation in BBB breakdown (Walker et al, 2010). Investigation into the mechanism of the anti-inflammatory action of vagus nerve stimulation has led to the formulation of the cholinergic antiinflammatory pathway (CAP) hypothesis in which vagus nerve activation indirectly stimulates nicotinic acetylcholine receptor ␣7 (nAChRa7) subunit on splenocytes, causing decreased production of proinflammatory cytokines (Pavlov and Tracey, 2006;Rosas-Ballina et al, 2011).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…More recent studies have implicated vagus nerve activity, especially the efferent splenic component, in reducing systemic inflammation (Borovikova et al, 2000;Rosas-Ballina et al, 2008;Olofsson et al, 2012). Consistent with this, we have previously demonstrated that splenectomy markedly decreased TBI-triggered BBB permeability, suggesting a role for spleen-mediated systemic inflammation in BBB breakdown (Walker et al, 2010). Investigation into the mechanism of the anti-inflammatory action of vagus nerve stimulation has led to the formulation of the cholinergic antiinflammatory pathway (CAP) hypothesis in which vagus nerve activation indirectly stimulates nicotinic acetylcholine receptor ␣7 (nAChRa7) subunit on splenocytes, causing decreased production of proinflammatory cytokines (Pavlov and Tracey, 2006;Rosas-Ballina et al, 2011).…”
Section: Introductionsupporting
confidence: 89%
“…A number of studies have investigated brain inflammation in response to TBI and its contribution to BBB pathology (Sanderson et al, 1999;Morganti-Kossmann et al, 2002;Titus et al, 2013;de Rivero Vaccari et al, 2016). These studies have shown a shift in microglia polarization toward the proinflammatory M1 subtype, astrocyte activation, and increased production of inflammatory cytokines in the injured tissue (Loane et al, 2014;Turtzo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulating peripheral inflammation can be a therapeutic target. In a traumatic brain injury model, multipotent adult progenitor cells exerted a neuroprotective effect through interaction with resident splenocytes [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Of note, Pati et al demonstrated in mouse models of TBI that mesenchymal stem cells exert perivascular protective effects to the penumbral BBB via increased junctional protein (VE-cadherin and occludin) expression [60]. Walker et al showed increased localization/organization of occludins to the microvasculature [61]. The Cox lab is currently using diffusion tensor MRI imaging to evaluate the response to cell therapy in acute setting for severe TBI in pediatric and adult clinical trials (NCT01851083 and NCT 01575470 respectively).…”
Section: Targets and Role Of Cellular Therapymentioning
confidence: 99%